Effect of on-screen text on multimedia learning with native and foreign-accented narration. (June 2020) - Chan, Kit Ying; Lyons, Claire; Kon, Lo Lo; Stine, Katelyn; Manley, Melissa; Crossley, Anthony
Abstract: This study examined the impact of redundant on-screen text on learning from an animated PowerPoint presentation, narrated either by a native or a foreign-accented narrator, with no text, summary text, or full text. Participants completed retention and transfer tests and rated the cognitive load induced by the narration and the PowerPoint materials. With a native narrator, participants performed better on transfer with no text than summary text ( redundancy effect ). The foreign-accented narration was perceived to be more difficult to understand. Transfer performance was worse for accented than native narration with no text, replicating a voice effect . With a foreign-accented narrator, participants performed better on retention with full text than summary text. Full text facilitated decoding of the accented narration at the word level, but it did not facilitate deep processing for knowledge transfer. The results are discussed in the context of cognitive load and the cognitive theory of multimedia learning . Highlights: Accented narration was perceived to be more difficult to understand. Content in the accented narration was harder to understand only with no text. No on-screen text resulted in better transfer performance during native narration. Full text resulted in better retention performance with foreign-accented narration. Full text prompted participants to process accented narration at the word level.